Upaya Indo-Europheesch Verbond dalam Memperjuangkan Kemandirian dan Status Sosial di Indonesia - Aulia Mutiara Putri; Rhoma Aria Dwi Yuliantri; Kuswono Kuswono; Kian Amboro; Nurul Ismi Lestari (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study aims to examine the struggle of the Indo Europeesch Verbond (IEV) in fighting for the existence, independence, and social recognition of Indo-Europeans in the Dutch East Indies. Indo-Europeans, as a group of European and indigenous descendants, were in an ambiguous social position—rejected by the Dutch and not fully accepted by the indigenous community. In the context of strong colonial discrimination, IEV emerged as an organization that voiced the interests of Indos through political and socio-economic channels. This study uses a qualitative method with a historical approach, through literature study, archival analysis, and interviews with descendants of IEV colonists in Giesting, Lampung. The results show that IEV played an important role in the Volksraad as an effort to fight for political rights and civil equality. In addition, the IEV colonization program in Giesting from 1926–1942 was a concrete step in establishing an independent and economically productive Indo community. However, the Japanese occupation in 1942 abruptly halted this project. This research concludes that IEV serves not only as an advocacy organization but also as a symbol of resistance against the marginalization of identity. This historical legacy demonstrates the importance of recognizing minority groups in the formation of an inclusive and multicultural nation.